A Management using Iddhipada IV for Patience Services following New Normal in Health Promotion Hospitals - Sonjai, Wanwisa (ASEAN Journal of Religious and Cultural Research, 2021)
This academic article presents the management concept in Health Promotion Hospitals for the benefit for patience services following New normal. After the Coronavirus Disease 2019 (COVID-19) by using Iddhipada IV, it consists of 4 principles which are 1) aspiration, 2) exertion, 3) thoughtfulness, and 4) investigation. The management concept used in this article consists of 5 principles which are 1) Planning, 2) Organizing, 3) Commanding, 4) Coordination, and 5) Controlling.